2009
DOI: 10.1073/pnas.0906263106
|View full text |Cite
|
Sign up to set email alerts
|

Competition between collective and individual dynamics

Abstract: Linking microscopic and macroscopic behavior is at the heart of many natural and social sciences. This apparent similarity conceals essential differences across disciplines: Although physical particles are assumed to optimize the global energy, economic agents maximize their own utility. Here, we solve exactly a Schellinglike segregation model, which interpolates continuously between cooperative and individual dynamics. We show that increasing the degree of cooperativity induces a qualitative transition from a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
135
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(140 citation statements)
references
References 19 publications
2
135
0
3
Order By: Relevance
“…Schelling thereby demonstrated that even weak individual preferences for homophily can give rise to strong segregation. This type of model has since been studied on networks, in continuous-space models, and analytically [37][38][39][40]. Previous versions of the Schelling model have been non-local in that agents have information about, and are able to move to, sites not immediately adjacent to them.…”
Section: Introductionmentioning
confidence: 99%
“…Schelling thereby demonstrated that even weak individual preferences for homophily can give rise to strong segregation. This type of model has since been studied on networks, in continuous-space models, and analytically [37][38][39][40]. Previous versions of the Schelling model have been non-local in that agents have information about, and are able to move to, sites not immediately adjacent to them.…”
Section: Introductionmentioning
confidence: 99%
“…that takes account of the number of ways of locating Rq red agents and Gq green agents in each block q of the city (Grauwin et al, 2009a).…”
Section: Main Result: Existence Of a Potential Functionmentioning
confidence: 99%
“…(iv) models of interacting socials agents, for which statistical physics approaches may be relevant in some cases [17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%